A brief review on recent advancement of tablet coating technology - Debgopal Ganguly; Soumyadip Ghosh; Pubali Chakraborty; Sumit Mitra; Shounak Chatterjee; Sarmistha Panja; Ananta Choudhury (Journal of Applied Pharmaceutical Research, 2022)
A tablet can be defined as a solid unit dosage form. There are several reasons for coating of solid dosage form, the most important reason is to control the release profile & also to control the bioavailability parameters of the APIs (Active Pharmaceutical Ingredients). Tablets containing active pharmaceutical ingredients (API) can be coated with thin polymer-based film for various advantages. Generally, horizontal rotating pans are used for coating purposes & coating solution can be spread through the spraying systems over the surface of tablets. Bitter taste masking, odor masking, physical and chemical protection, and also environmental protection are all benefits of the tablet coating. Despite that, Tablet coating also plays an important role in controlling the action site. Sugar-coating, film coating, and enteric coating are some of the conventional tablet coating processes. The primary objective for creating tablet coating technologies is to eliminate the numerous disadvantages of solvent-based coating. Coating solution preferentially applied on the surface of solid dosage forms without the need for any solvent in these novel technologies. This review article provides information regarding the techniques of conventional tablet coating, the recent advancement of tablet coating procedures, and tablet coating components.